ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PEMERINTAH KOTA SURAKARTA TAHUN ANGGARAN 2014 – 2018 - Rustanto, Eka Arif; Suseno, Y. Djoko; Sriwidodo, Untung (Universitas Slamet Riyadi, 2020)
This research aims to know (1) The financial performance of the Surakarta city government fiscal year period 2014 - 2018, (2) efficiency of the expenditure of Surakarta city government in the management of its resources year budget 2014 - 2018. The population in this research is the realization report of the Government of Surakarta. The samples studied were the realization report of the Government of Surakarta APBD year budget from 2014 to 2018. Sample editing using the Purposive sampling method. The source of the research data is secondary data. The data analysis techniques used are quantitative descriptive. The conclusion of the research: hypotheses that declare the financial performance of the Surakarta city government year period budget 2014 - 2018 views from (1) fiscal decentralization degree ratio is sufficient, is true, (2) PAD effectiveness ratio is effective, is true and (3) ratio effectiveness of PAD is effective, is true. Hypotheses that state Surakarta's government spending efficiency in its resource management year 2014 - 2018 budget is an efficient view of the (1) ineffective efficiency ratio, which is not true, (2) ineffective shopping efficiency ratio, So it is not true, (3) large operating spending ratio, so it is not true and (4) small capital expenditure ratio, so it is not true.